Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4103/jcvjs.jcvjs_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute combined fractures of the atlas and axis: A retrospective study of two trauma centers

Abstract: Background:Management of combination fractures of the atlas and axis varies from nonoperative immobilization to selective early surgical intervention. In this study, we present our experience in managing these injuries.Materials and Methods:Electronic databases from two level 1 trauma centers were queried to identify all patients diagnosed with C1-C2 combination fractures from 2009 to present. Patient demographics, fracture characteristics, treatment modality, complications, Frankel scores, and fusion status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The 22 articles identified during our literature review were published from 1977 to 2022, totaling 230 patients. A description of each article is presented in Table 1 [ 1 , 4 , 8 , 9 , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. There were 12 case series, 7 case reports, and 3 retrospective reviews.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 22 articles identified during our literature review were published from 1977 to 2022, totaling 230 patients. A description of each article is presented in Table 1 [ 1 , 4 , 8 , 9 , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. There were 12 case series, 7 case reports, and 3 retrospective reviews.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of 221 patients with reported data was 58 years. Only 2 studies reported on comorbidities, which included hypertension, myocardiopathy, diabetes, cerebrovascular accident, hypothyroidism, and smoking [ 8 , 22 ]. Thirty-seven of the 213 patients (17%) presented with neurologic deficits, which is consistent with previously reported data [4] , [5] , [6] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations